Characterization of the bZIP Transcription Factor Family in Pepper (Capsicum annuum L.): CabZIP25 Positively Modulates the Salt Tolerance - Gai, Wen-Xian; Ma, Xiao; Qiao, Yi-Ming; Shi, Bu-Hang; ul Haq, Saeed; Li, Quan-Hui; Wei, Ai-Min; Liu, Ke-Ke; Gong, Zhen-Hui (Frontiers in Plant Science, 2020)
The basic leucine zipper (bZIP) proteins compose a family of transcription factors, which play a crucial role in plant growth, development, and abiotic and biotic stress responses. However, no comprehensive analysis of bZIP family has been reported in pepper (Capsicum annuum L.). In this study, we identified and characterized 60 bZIP transcription factor-encoding genes from two pepper genomes. These genes were divided into 10 groups, based on their phylogenetic relationships with bZIP genes from Arabidopsis. Five intron/exon structural patterns within the basic and hinge regions were defined and the conserved motifs were also identified among all pepper bZIP proteins, which have helped classify them into different subfamilies and support the group classification. Based on the transcriptomic data of Zhunla-1 genome, genome-wide expression analysis of 59 pepper bZIP genes (not including CabZIP25 of CM334 genome), indicated that the pepper bZIP genes were differentially expressed in pepper tissues and developmental stages, and many of pepper bZIP genes might be involved in responses to various abiotic stresses and phytohormones. Further, expression analysis using quantitative real-time PCR (qRT-PCR) showed that CabZIP25 gene was expressed at relatively higher levels in vegetative tissues, and strongly induced by abiotic stresses and phytohormones. In comparing with wild type Arabidopsis, germination rate, fresh weight, chlorophyll content, and root length were increased in CabZIP25-overexpressing Arabidopsis under salt stress. Additionally, CabZIP25-silenced pepper showed lower chlorophyll content than control plants under salt stress. These results suggested that CabZIP25 improved the salt tolerance in plants. Taken together, this information provides new opportunities for functional characterization of bZIP transcription factors in pepper.